(3cJGH GdSHYjGJs - (3eMeO Hf YHO GdQMef Hf YHO Gddg GdgeOGfj, CHh fUQs ((3eMeO Hf UdGM GdMJei s)
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdLHGQ GYde Cf GdNGdb GdHGQF LdJ bOQJg hYdJ cdeJg GdCTjGA GdSHYI HGdBTjGA GdSHYI Ke Rjf Jdc GdSHYI HSHYI CNQi s
(3BNQgG (B:s
(3bGd GdLeYI hGdLfI dc aGYWjJ GdLfI hGdLeYI dCeJc hQVGi eY GdLfI hGdLeYI hGdMeO ddg Ydi GdJeGe hGdceGd Je GdcJGH HMeO Gddg JYGdi hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B3s
(3GdfSNI HgG MhGTs
(3HBNQgG fbhd eNJdaIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdeJMa GdYQGbi (B_ (3HZOGO (B(2097) s
Keywords: (3GdeLGejYs